Strategies to Improve Overhead Passing Skills in Volleyball through the Demonstration Teaching Method: Strategi Meningkatkan Keterampilan Passing Atas dalam Permainan Bola Voli melalui Metode Pembelajaran Demonstrasi - Nurhasanah Nurhasanah; Gunawan Gunawan; Addriana Bulu Baan; Mursalim Mursalim (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2025)
Basic motor skills in volleyball, such as overhead passing, play an important role in supporting overall game success. However, in reality, many students have difficulty mastering this technique correctly. This study aims to improve learning outcomes in the overhead passing skill in volleyball through the application of the demonstration learning method among Grade XI students at SMANOR Palu. The research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. In the pre-cycle stage, only 8 students (40%) achieved the minimum learning mastery, while 12 students (60%) had not. After implementing the demonstration method in Cycle I, there was an improvement in learning outcomes, with 12 students (60%) achieving mastery and 8 students (40%) still not meeting the standard. Despite this improvement, Cycle II was carried out to optimize the results further. The results of Cycle II showed a significant increase, with 18 students (90%) achieving learning mastery and only 2 students (10%) remaining below the standard. The demonstration method proved effective as it provided a clear visualization of movements, making it easier for students to understand and accurately imitate the basic technique of overhead passing. In addition, immediate feedback after the demonstration helped students quickly correct technical errors. Therefore, the demonstration method is effective in enhancing students' overhead passing skills.